Sequence Analysis of Native Oligosaccharides Using Negative ESI Tandem MS - Zhang, Zhenqing (2009)
Carbohydrates exhibit many physiologically and pharmacologically important activities, yet their complicated structure and sequence pose major analytical challenges. Although their structural complexity makes analysis of carbohydrate difficult, mass spectrometry (MS) with high sensitivity, resolution and accuracy has become a vital tool in many applications related to analysis of carbohydrates or oligosaccharides. This application is essentially based on soft ionization technique which facilitates the ionization and vaporization of large, polar and thermally labile biomolecules. Electrospray-ionization (ESI), one of the soft ionization technique, tandem MS has been used in the sequencing of peptides, proteins, lipids, nucleic acids and more recently carbohydrates. The development of the ESI and tandem MS has begun to make carbohydrate analysis more routine. This review will focus on the application of the ESI tandem MS for the sequence analysis of native oligosaccharides, including neutral saccharides with multiple linkages, and the uronic acid polymers, alginate and glycosaminoglycans structures containing epimers.